Kemandirian dan Motivasi Belajar Siswa Terhadap Prestasi Belajar Program Keahlian Akuntansi Di SMK Negeri 1 Sidenreng Rappang - Sahade Sahade (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2020)
This study aims to determine the effect of independence and learning motivation on student achievement in accounting expertise program at SMK Negeri 1 Sidrap. The population in this study were 66th grade students of the Accounting Skills Program, amounting to 66 students. Data analysis used descriptive analysis, classic assumption test, instrument test and hypothesis test with non-parametric statistics. The results of this study indicate that learning independence and motivation influence student achievement with a significant level < 0.05. The coefficient of determination (R2) is 0.538 or 53.8 percent. This means that students who have high independence and motivation to learn in accounting subjects will be able to improve student learning achievement itself by 53.8 percent while the remaining 46.2 percent is influenced by other factors beyond observation in this study. The increase in student achievement is dominated by learning independence with a coefficient of determination of 0.471 or 47 percent